Penerapan Dakwah Kontemporer dalam Formulasi Qanun Syariah Aceh - Hasibuan, Susanti; Arianto, Nanang (Idarotuna, 2025)
Abstract: TThe implementation of Qanun Syariah in Aceh is considered something of a dilemma.  The implementation of Qanun is considered to violate the provisions of Indonesian positive law, in process of Qanun, the Al-Quran and Hadith are used as a basis, and it contains repressive da'wah, da'wah by making the government of structural da'wa, can pressure the public to obey the Islam.  The qualitative method in this research focuses on activities, relationships, situations and conditions in the field. In carrying out this research, author went directly to institutions related to the implementation of Qanun Islamic Sharia in Aceh in Wilayatul Hisbah, Islamic Sharia, Governor, DPRA, MPU, Ministry of Law and Human Rights. The results is state that Qanun Syariah according to Khaled Abou el Fadl is a contemporary form of da'wah that is included in government structures. Banda Aceh has the authority in accordance with the legitimacy of the State.